Evaluation of certain food additives : sixty-third report of the Joint FAO/WHO Expert Committee on Food Additives (WHO, 2005)
This report represents the conclusions of a Joint FAO/WHO Expert Committee met in Geneva, 8-17 June 2004. The tasks before the Committee were: to elaborate further principles for evaluating the safety of food additives and contaminants; to undertake toxicological evaluations of certain food additives and flavouring agents; to review and prepare specifications for selected food additives and flavouring agents; and to undertake a toxicological evaluation of a natural constituent, glycyrrhizinic acid.
WHO technical report series, ISSN 0512-3054 928
Keywords: zemědělství a potravinářství; Food Additives; Flavoring Agents; hygiena; toxikologie; hodnocení rizik; chuťové esence; kontaminace potravin; potravinářské přísady; Risk Assessment; Food Contamination; nutriční terapie, dietoterapie a výživa